Statistical Monitoring of Clinical Trials Fundamentals for Investigators - Moyé, Lemuel A. (Springer New York : Imprint: Springer, 2006)
Statistical Monitoring of Clinical Trials: Fundamentals for Investigators introduces the investigator and statistician to monitoring procedures in clinical research. Clearly presenting the necessary background with limited use of mathematics, this book increases the knowledge, experience, and intuition of investigations in the use of these important procedures now required by the many clinical research efforts. The author provides motivated clinical investigators the background, correct use, and interpretation of these monitoring procedures at an elementary statistical level. He defines terms commonly used such as group sequential procedures and stochastic curtailment in non-mathematical language and discusses the commonly used procedures of Pocock, O'Brien-Fleming, and Lan-DeMets. He discusses the notions of conditional power, monitoring for safety and futility, and monitoring multiple endpoints in the study. The use of monitoring clinical trials is introduced in the context of the evolution of clinical research and one chapter is devoted to the more recent Bayesian procedures. Dr. Lemuel A. Moyé, M.D., Ph.D. is a physician and a biostatistician at the University of Texas School of Public Health. He is a diplomat of the National Board of Medical Examiners and is currently Professor of Biostatistics at the University of Texas School of Public Health in Houston where he holds a full time faculty position. Dr. Moyé has carried out cardiovascular research for twenty years and continues to be involved in the design, execution and analysis of clinical trials, both reporting to and serving on many Data Monitoring Committees. He has served in several clinical trials sponsored by both the U.S. government and private industry. In addition, Dr. Moyé has served as statistician/epidemiologist for six years on both the Cardiovascular and Renal Drug Advisory Committee to the Food and Drug Administration and the Pharmacy Sciences Advisory Committee to the FDA. He has published over 120 manuscripts in peer-reviewed literature that discuss the design, execution and analysis of clinical research. He authored Statistical Reasoning in Medicine: The Intuitive P-value Primer (Springer, 2000) and Multiple Analysis in Clinical Trials: Fundamentals for Investigators (Springer, 2003).